Acculturation and Career Intention: Chinese Overseas Students in the United Kingdom - LIANG, LIYING (2016)
This paper aims to find out the acculturation situation of Chinese overseas students in the United Kingdom (UK) and explore the relationship between their acculturation degree and career intention of working in the UK. The acculturation part mainly focuses on discussing Chinese overseas students’ general acculturation in daily life, academic life and interaction with non-Chinese people. Findings of interview reveal that they have a better acculturation in general adjustment of various aspects of daily life (referring to the diet, weather, etc.) and academic life in the UK, while they have difficulties in coping with non-Chinese people during the acculturation process. The findings also suggest that Chinese overseas students express an intense intension of working in the UK concerning their decent acculturation ability and degree towards British culture and environment as well as various kinds of preferred UK culture, but the availability of the working visa in the UK makes them give up the thought.